Hubungan GCG (Good Corporate Governance) Dengan Etika Bisnis, Pedoman Perilaku, dan Manajemen Risiko Pada PT. Arthapura Global Konstruksi - Nurdiansyah, Dian Hakip; Anita, Widya Febryari; Fathia, Siti Diana; Marpaung, Gerald Matthew (EBBANK, 2024)
Corporate Governance is a system that guarantees all stakeholders that they will obtain their rights that are reasonable and of high value. PT. Arthapura Global Construction is a company that operates in the fields of construction, engineering, and procurement. This company recognizes the importance of the implementation of corporate governance as one of the tools to increase the value of business progress. This study aims to present information about GCG (Good Corporate Governance) related to business ethics, code of conduct, and risk management at PT. Arthapura Global Construction. The research method used is a qualitative descriptive method. This study uses a sample of Construction Services Companies domiciled in Depok City with the research subjects of Commissioners, Directors, Employees/Workers, and other stakeholders such as suppliers, business partners, or customers who have business interactions with the company. The result of this study is that PT. Arthapura Global Construction implements Good Corporate Governance (GCG) related to business ethics, code of conduct, and risk management. Where companies apply various kinds of business ethics principles. PT. Arthapura Global Construction is designed to influence, shape, regulate and perform appropriate behaviors, so as to achieve consistent outputs that are in accordance with the Company's work culture.